Interesterification Does Not Alter Postprandial Absorption or Oxidation of Dietary Fats, as Measured Using Stable Isotopes Analysis (P08-104-19). (24th October 2019) - Harding, Scott; Hall, Wendy; Mills, Charlotte; Fielding, Barbara; Gray, Robert; Bruce, Johanna; Berry, Sarah
Abstract: Objectives: Altering the structure of lipids by interesterification is largely replacing partial hydrogenation in the production of solid form vegetable-based fats. While proposed to be much healthier than the trans-fat containing alternatives, very little mechanistic work has been done to determine how these interesterified (IE) fats act in the human body. This study aimed to describe the physiological handling of commonly consumed IE fats during and after digestion compared to a non-IE equivalent and a control oil. Methods: In a randomized, double-blinded controlled trial, healthy adults ( n = 20) aged 45–75 years were assessed for postprandial triglyceride (TG) responses following consumption of 3 test meals (897 kcal, 50 g fat, 16 g protein, 88 g carbohydrate). Each meal contained 50 g of IE fat (80:20 palm stearin/palm kernel fat), the equivalent non-IE fat, or high-monounsaturated oil (canola oil, CO). A subsample of the study group ( n = 9) consumed 75 mg of 1– 13 C glyceryl tripalmitate to trace the metabolic fate of the saturated fats consumed. Blood and breath samples were collected at baseline, and hourly thereafter for 8 h. Samples were analyzed for 13 C: 12 C ratio by isotope ratio mass spectrometry and expressed as % dose recovered (PDR). Results: No differences were observed for palmitate oxidation as measured by PDR in breath CO2 . Similarly, no difference in PDR of plasma 13 C-palmitate in the postprandial period was observed between IE or non-IE fats ( P = 0.439). Recovery of 13 C-palmitate was ∼2.5-fold higher for the CO versus non-IE and IE treatments ( P < 0.0001). We speculate this difference was due mainly to the differences in total solid fats at body temperature (37°C) and possibly the higher 13 C-palmitate: total palmitate ratio in the CO meal. The levels of solid fat at 37°C were 21%, 16% and 0% for non-IE, IE and CO, respectively. As a function of the total palmitate found in the 50 g of fats consumed, non-IE, IE and CO were labelled with 13 C palmitate at 0.26%, 0.26%, and 2.3%, respectively. While it is unlikely tracer enrichment was responsible, both factors may have collectively contributed to the higher isotope recovery in the CO meal. Conclusions: Rates of palmitate absorption and oxidation were not affected by interesterification. The degree of saturation likely affect absorption due to the proportion of solid fat at body temperature. Funding Sources: BBSRC DRINC (UK). Supporting Tables, Images and/or Graphs